Deprotonation of lipid-depleted bacteriorhodopsin. - Jang, D J (1988)
The removal of 75% of the lipid from bacteriorhodopsin caused the following: (i) decreased efficiency and rate of deprotonation of the protonated Schiff base (as monitored by absorption of the M412 intermediate); (ii) increased efficiency of deprotonation of deionized samples; (iii) a decrease by 1 unit in the pH at which deprotonation ceases; (iv) increased intensity of Eu3+ emission in Eu3+-regenerated deionized delipidated samples; (v) increased exposure of the Eu3+ sites to water; and (vi) elimination of the dependence of the deprotonation efficiency on the metal cation concentration. These results are discussed in terms of changes in the protein conformation upon delipidation, which in turn control the deprotonation mechanism.